The Impact of Distance Learning Media on the Educational Process of Learners During the Pandemic - Margareth Sylvia Saborofek; Myristica Imanita; Fitra Saleh; Eko Lianto Rihardi (HK-Publishing, 2022)
AbstractThe covid-19 disease has become a scourge of international life. All aspects of life are affected by it, from economic, social, religious, political, and environmental elements. There is no exception in Indonesia. One way to break the spread of the covid-19 chain is by transforming the education system into a virtual and carried out in their own homes. The purpose of this research is to know the impact of distance learning media on the education process of learners. The approach used in this study is qualitative data collection techniques with literature studies. From the search results, the author divides into three major themes, namely (1) inefficiency in online learners (2). The provision of materials submitted by lecturers is not fully understood (3). The lecturer only listened and did not respond.Keywords: Covid-19, Impact, Online learning. AbstrakPenyakit covid-19 telah menjadi momok kehidupan internasional. Semua aspek kehidupan dipengaruhi olehnya, mulai dari elemen ekonomi, sosial, agama, politik, dan lingkungan. Tak terkecuali di Indonesia. Salah satu cara memutus mata rantai penyebaran covid-19 adalah dengan mentransformasikan sistem pendidikan menjadi virtual dan dilaksanakan di rumah masing-masing. Tujuan penelitian ini adalah untuk mengetahui pengaruh media pembelajaran jarak jauh terhadap proses pendidikan peserta didik. Pendekatan yang digunakan dalam penelitian ini adalah teknik pengumpulan data kualitatif dengan studi kepustakaan. Dari hasil penelusuran, penulis membagi menjadi tiga tema besar, yaitu (1) inefisiensi dalam pembelajar online (2). Pemberian materi yang disampaikan oleh dosen belum sepenuhnya dipahami (3). Dosen hanya mendengarkan dan tidak menanggapi.Kata kunci: Covid-19, Dampak, Pembelajaran daring.